Restauro e reabilitação do prédio da antiga faculdade de direito da Universidade Federal do Amazonas - Messias, Aylla Emanuelle Silveira de (Brasil, 2022)
Final graduation document of the Architecture and Urbanism course of the Federal University of Amazonas, proposes the Restoration and Rehabilitation of the building of the old faculty of law of the UFAM, an exercise accomplished applying a clear methodology, following the manual of elaboration of cultural heritage preservation projects, a 2005 publication of the Monumenta Program, prepared by the union, through the National Institute of Historic and Artistic Heritage (IPHAN). From this, the need to recover the integrity and valuation of the property was created, aiming at a restoration and rehabilitation project, with a new beginning, leading patrons to appropriate themselves as people, joining historical, scientific and cultural values, being relevant to society and academia. With this publication, it is expected that students and researchers will complement their knowledge regarding the process of a built heritage asset, in search of its adequacy to the present time and to the current urban dynamics. Keywords: Architecture; Restoration; Rehabilitation.